Measuring customer loyalty using perceptions of trust, service quality, and switching costs as well as customer satisfaction in the life insurance industry – a replication study - Chipp, Kerry (University of Pretoria, 2022)
Mini Dissertation (MBA)--University of Pretoria, 2021.